Teknologi Informasi sebagai Media Pembelajaran Digital untuk Menguatkan Literasi Digital Mahasiswa - Ananda, Rizki (Yayasan Nanggroe Aceh Mulia, 2025)
The development of information technology has significantly transformed the education sector, particularly in higher education learning processes. Digital literacy has become an essential skill for students to access, process, and critically evaluate information. This article aims to examine the role of information technology as a digital learning medium to strengthen students' digital literacy in the era of the fourth industrial revolution. The research method employed is library research, which involves analyzing various relevant literature, including scientific journals, books, and research reports. The findings indicate that information technology, through the use of digital learning platforms such as Learning Management Systems (LMS), online conferencing applications, and digital academic resources, enhances students’ independent learning, creativity, and critical thinking skills. The study also highlights challenges, including digital skill gaps and limited infrastructure in certain regions. The conclusion emphasizes that the integration of information technology in learning not only strengthens students' digital literacy but also serves as a strategic instrument for developing adaptive and technologically literate academic generations.